H‐Doped Black Titania with Very High Solar Absorption and Excellent Photocatalysis Enhanced by Localized Surface Plasmon Resonance. (17th May 2013) - Wang, Zhou; Yang, Chongyin; Lin, Tianquan; Yin, Hao; Chen, Ping; Wan, Dongyun; Xu, Fangfang; Huang, Fuqiang; Lin, Jianhua; Xie, Xiaoming; Jiang, Mianheng
Abstract Black TiO2 attracts enormous attention due to its large solar absorption and induced excellent photocatalytic activity. Herein, a new approach assisted by hydrogen plasma to synthesize unique H‐doped black titania with a core/shell structure (TiO2@TiO2‐xHx) is presented, superior to the high H2‐pressure process (under 20 bar for five days). The black titania possesses the largest solar absorption (≈83%), far more than any other reported black titania (the record (high‐pressure): ≈30%). H doping is favorable to eliminate the recombination centers of light‐induced electrons and holes. High absorption and low recombination ensure the excellent photocatalytic activity for the black titania in the photo‐oxidation of organic molecules in water and the production of hydrogen. The H‐doped amorphous shell is proposed to play the same role as Ag or Pt loading on TiO2 nanocrystals, which induces the localized surface plasma resonance and black coloration. Photocatalytic water splitting and cleaning using TiO2‐xHx is believed to have a bright future for sustainable energy sources and cleaning environment.